A PI based coordinated maximum power point tracking controller for grid connected photovoltaic system / Md Haidar Islam - Md Haidar, Islam (2021)
The global demand for electric energy has continuously increased over the last few decades. Photovoltaic (PV) sources are predicted to become one of the biggest contributors to electricity generation among all renewable energy generation candidates by 2040. The photovoltaic system a renewable energy source that has attracted the attention of researchers in recent years. The power output of a photovoltaic system has a complex dependence on varying environmental conditions such as solar irradiation and ambient temperature which cannot be controlled, thereby making the current versus voltage (I-V) and power versus voltage (P-V) characteristics of photovoltaic arrays nonlinear. Therefore, maximum power varies from time to time as these factors change rapidly. In order to maintain maximum power of the PV system, maximum power point tracking (MPPT) techniques are incorporated with direct current to direct current (DC-DC) converters and proportional integral (PI) controllers. A MPPT is an automatic control algorithm used to adjust the power interfaces and achieve the maximum possible power harvest, during instantaneous deviations of light levels, shading, temperature, and photovoltaic module characteristics. The idea behind the MPPT techniques is to adjust an operating voltage close to a maximum power point (MPP) under constantly changing atmospheric conditions. The MPPT techniques vary in many aspects such as: digital or analogical implementation, tracking speed, convergence speed, cost, simplicity and in other aspects. The differences between conventional and other modified MPPT algorithms are explained in this research work. A new coordinated PI-MPPT algorithm is then proposed based on the deficiencies of the other algorithms. The proposed MPPT algorithm is used to maximize a conversion efficiency of a PV array. The proposed algorithm’s reference variables such as current, voltage, duty cycle and power output will be traced and the results obtained for different weather conditions. The proposed algorithm enhances the steady-state and dynamic responses by introducing an improved adaptive step-size for updating variables. A low complexity grid synchronization controller is implemented to generate parallel and orthogonal components of the grid voltage in a highly computationally efficient manner in order to create a synchronized current reference to the current control loop. MATLAB Simulink tool box is used to create models to carry out performance evaluation of a PV module with the MPPT algorithms. The grid-connected PV system is implemented with dSPACE controller and solar simulator, and other measuring instruments. Theoretical demonstrations are verified by the simulation and experimental results of the proposed system. The measured results validated that the proposed coordinated PI-MPPT technique tracks reference values accurately. The power efficiency of the proposed algorithm is achieved by 99.92%, 99.8%, 99.88% and 99.83% against uniform weather, partial shading conditions (PSCs) 1, 2 and 3, respectively, which is much higher than that of conventional MPPT techniques. The proposed system is an improved method which designed and modeled to obtain good accuracy and stability of tracking GMPP under highly dynamic conditions.